2021
DOI: 10.1016/j.euros.2020.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Active Surveillance—Is It Feasible for Intermediate-risk Localised Prostate Cancer?

Abstract: Background Although active surveillance (AS) is a well-recognised treatment option for localised low-risk prostate cancer (LRPC), its role in the management of localised intermediate-risk prostate cancer (IRPC) is not clear yet and the available literature is slightly contradictory. Objective To compare the outcome of AS between LRPC and IRPC patients. Design, setting, and participants Between November 2002 and August 2019, 372 men with local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Rather than defining a single criterion that can identify IR patients suitable for AS, there is promise in better understanding individual patient risk through multiple parame- ) during AS will help refine the selection of IR patients. Mukherjee et al [28] reported that as an initial stratification tool, MRI was useful in excluding patients with large-volume tumors (eg, Prostate Imaging Reporting and Data System score 5) from AS, and further studies are needed to determine whether better outcomes can be achieved in patients with no visible tumors or low-volume tumors on MRI. As a surveillance tool, progression on MRI was the trigger for definitive treatment in 14% [18] to 70.4% [15] of cases treated during follow-up, and future studies are needed to demonstrate whether MRI is useful in indicating early treatment before clinical progression.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Rather than defining a single criterion that can identify IR patients suitable for AS, there is promise in better understanding individual patient risk through multiple parame- ) during AS will help refine the selection of IR patients. Mukherjee et al [28] reported that as an initial stratification tool, MRI was useful in excluding patients with large-volume tumors (eg, Prostate Imaging Reporting and Data System score 5) from AS, and further studies are needed to determine whether better outcomes can be achieved in patients with no visible tumors or low-volume tumors on MRI. As a surveillance tool, progression on MRI was the trigger for definitive treatment in 14% [18] to 70.4% [15] of cases treated during follow-up, and future studies are needed to demonstrate whether MRI is useful in indicating early treatment before clinical progression.…”
Section: Discussionmentioning
confidence: 99%
“…9) relative to LR patients. Among the studies (n = 4) that compared the risk of PCa death in LR and IR patients, there were no PCa-related deaths in either group [26][27][28]31]. Allcause deaths were assessed in two studies [28,31].…”
Section: 6mentioning
confidence: 99%
See 2 more Smart Citations
“…Most of these initiatives have mainly included men with classical low-risk disease with progression to grade group 2 as the end point. However, there is increasing recognition that grade group 2/favourable intermediate-risk/CPG2 disease is also suitable for management with AS, and this has been endorsed by national guidelines [1] , [4] , [28] , [29] , [30] . These men have a higher risk of progression (as we have shown in this study) and hence require closer follow-up, but the majority will do very well.…”
Section: Discussionmentioning
confidence: 99%